The effectiveness of psychological intervention for women who committed child sexual abuse: an empty systematic review - Sousa, Marta (2024)
The topic of sex offenses committed by women has received relatively little attention until recent decades. The scarcity of research in this domain underscores the urgent need for a more comprehensive understanding and effective interventions. Women who committed child sexual abuse (CSA) exhibit a distinct psychological profile compared to men, requiring specific intervention programs. The current systematic review has two aims: the primary aim is to analyze the effectiveness of psychological interventions with women who committed CSA, and the secondary aim is to identify the intervention models and strategies used with them. Six databases were searched for studies examining the effectiveness of psychological interventions. All retrieved papers were excluded after full-text assessments as none met the primary objective. However,eight publications fulfilled the secondary objective of identifying models and strategies that could inform intervention development. The intervention programs presented addressed specific targets focused on criminogenic needs highlighted in the literature as central to this population, as well as targets that complement the intervention according to individual characteristics. Moreover, the studies frequently emphasize an intervention approach centered on individuals’ potential (and not just their deficits), employing a gender paradigm to underpin psychological interventions with this population. The results of this review highlight a major gap in the current literature concerning both the delivery and effectiveness assessment of psychological intervention for women who committed CSA. The studies incorporated for the second objective elucidated critical treatment targets and models to inform intervention strategies, which are subsequently discussed in terms of their practical implications.